Birth companionship in a government health system: a pilot study in Kigoma, Tanzania - Paul Chaote; Nguke Mwakatundu; Sunday Dominico; Alex Mputa; Agnes Mbanza; Magdalena Metta; Samantha Lobis; Michelle Dynes; Selemani Mbuyita; Shanon McNab; Karen Schmidt; Florina Serbanescu (BMC, 2021)
Abstract Background Having a companion of choice throughout childbirth is an important component of good quality and respectful maternity care for women and has become standard in many countries. However, there are only a few examples of birth companionship being implemented in government health systems in low-income countries. To learn if birth companionship was feasible, acceptable and led to improved quality of care in these settings, we implemented a pilot project using 9 intervention and 6 comparison sites (all government health facilities) in a rural region of Tanzania. Methods The pilot was developed and implemented in Kigoma, Tanzania between July 2016 and December 2018. Women delivering at intervention sites were given the choice of having a birth companion with them during childbirth. We evaluated the pilot with: (a) project data; (b) focus group discussions; (c) structured and semi-structured interviews; and (d) service statistics. Results More than 80% of women delivering at intervention sites had a birth companion who provided support during childbirth, including comforting women and staying by their side. Most women interviewed at intervention sites were very satisfied with having a companion during childbirth (96-99%). Most women at the intervention sites also reported that the presence of a companion improved their labor, delivery and postpartum experience (82-97%). Health providers also found companions very helpful because they assisted with their workload, alerted the provider about changes in the woman's status, and provided emotional support to the woman. When comparing intervention and comparison sites, providers at intervention sites were significantly more likely to: respond to women who called for help (p = 0.003), interact in a friendly way (p < 0.001), greet women respectfully (p < 0.001), and try to make them more comfortable (p = 0.003). Higher proportions of women who gave birth at intervention sites reported being "very satisfied" with the care they received (p < 0.001), and that the staff were "very kind" (p < 0.001) and "very encouraging" (p < 0.001). Conclusion Birth companionship was feasible and well accepted by health providers, government officials and most importantly, women who delivered at intervention facilities. The introduction of birth companionship improved women's experience of birth and the maternity ward environment overall.